1999
DOI: 10.1017/s0890037x00044882
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Green and Yellow Foxtail (Setaria viridisandS. glauca) Seed Production Following Spring Wheat (Triticum aestivum) Harvest

Abstract: Green and yellow foxtail seed production following harvest of spring wheat is a concern of producers in the northern Great Plains of the United States and the Prairie Provinces of Canada. Experiments were conducted in 1996 and 1997 in three tillage systems, no till (NT), chisel plow (CP), and moldboard plow (MP), at the University of Minnesota West Central Experiment Station, Morris, MN, to determine whether time of glyphosate application or tillage after spring wheat harvest could reduce postharvest foxtail s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
(11 reference statements)
1
18
0
Order By: Relevance
“…Management treatments administered early in the growing season had little to no effect on foxtail seed production after spring wheat harvest, which mimics the results reported earlier (Kegode et al 1999). There are two interesting features regarding postharvest seed production.…”
Section: Foxtail Panicle Lengthsupporting
confidence: 85%
See 2 more Smart Citations
“…Management treatments administered early in the growing season had little to no effect on foxtail seed production after spring wheat harvest, which mimics the results reported earlier (Kegode et al 1999). There are two interesting features regarding postharvest seed production.…”
Section: Foxtail Panicle Lengthsupporting
confidence: 85%
“…For example, Kegode et al (1999) found that either tillage or glyphosate application within 10 d after wheat harvest lowered foxtail seed production considerably. Even though tillage after wheat harvest can result in burial of weed seeds, it also minimizes foxtail regeneration and consequently lowers the overall foxtail seedbank (Eyherabide and Calvino 2000).…”
Section: Foxtail Panicle Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Green foxtail and yellow foxtail are important weeds in many crops grown in North America, and they are known to produce numerous seeds (Kegode et al 1999a(Kegode et al , 1999b(Kegode et al , 2003Santelmann et al 1963;Vanden Born 1971). Because factors regulating foxtail seed production are poorly understood, there is a need to determine the magnitude of seed production of plants that escape control.…”
mentioning
confidence: 99%
“…This level of fecundity is more than enough to replenish the seedbank. Identical processes occur after spring wheat harvest in the Corn Belt with foxtails ( Setaria spp),62 and almost certainly they occur in all other cropped fields as well. In many instances lush maturing crops will hide smaller seed‐bearing weeds and, thereby, lull managers into a false sense of accomplishment.…”
Section: Ars Researchmentioning
confidence: 99%